Sequência didática para abordagem em física sobre radiações solares do tipo ultravioleta e fotoproteção - Oliveira, Antonio Carlos de (2019)
Everyday life promotes learning opportunities in view of the various phenomena present in our lives, including those related to physics. Therefore, the physical concepts approached in the classroom must have connection with the student's experience. This dissertation had as its main objective to elaborate an educational product to be applied in high school classes. The elaborated product is a teaching sequence (TS) focused on a science-technology-society (STS) approach. The purpose of the TS is promoting the learning of physical concepts related to electromagnetic waves, including electromagnetic radiation emission spectrum, with emphasis on ultraviolet radiation, and the importance of photoprotection for human health. The TS focuses more on issues related to ultraviolet solar radiation, its interference with people's health, including the risks, benefits and care that must be taken to protect against such radiation. The activities were applied to two third-year high school classes in a public school in the metropolitan region of Aracaju, SE. Among the TS's activities, there was also the presentation of the basic components, assembly and use of a handcrafted spectrophotometer, constructed with materials easily acquired. This equipment was used to quantify the absorption levels of sunscreens, as a function of the wavelength of the radiation incident on them. This made it possible to relate the effectiveness of using the sunscreens against the effects of ultraviolet radiation. The activities contributed to motivate the students in the acquisition of physical concepts relevant to the content addressed. The triad that makes up the teaching sequence, structured by scientific conceptualization, use of technology and social implications, contemplates an STS approach.